(untitled) (Международный научный журнал «Инженер», 2026)
The article develops the design of a mobile protective structure depending on the trajectory of the stones to protect the railway track from stones. The use of mobile protective structures chosen to protect the railway track from external influences is justified, taking into account the trajectory, flight range, height of falling stones from the mountain and the value of impact dynamic forces arising from a collision with the structure. Also, various designs of mobile protective structures are presented, while taking into account the possibility of moving structures from an inactive rockfall site to an active one and obtaining lower costs from an economic point of view.